A ANALISIS PERAN MUNAS TARJIH MUHAMMADIYAH KE-31 TERHADAP PENETAPAN WAKTU SALAT SUBUH DI MAKASSAR - Wakia, Nurul; Sabriadi; Amir, Rahma; Putri Aulia, Musfira Ananda (UIN ALAUDDIN MAKASSAR, 2025)
This study examines the role of the 31st Muhammadiyah Tarjih National Conference on the determination of the dawn prayer time in Makassar, where there is no uniformity in the application of the dawn time, especially related to the adjustment of the time based on the decision of the 31st Muhammadiyah Tarjih National Conference. The focus of this study is to identify the public response and the method of determining the law used by the Tarjih National Conference in determining the criteria for the dawn prayer time. This study is a field research with a qualitative descriptive type and uses a sharia and historical approach. Data were collected through interviews, observations and literature studies, then analyzed using data reduction techniques, data presentation and drawing conclusions. The results of the study indicate that the determination of the initial time for the dawn prayer in Muhammadiyah mosques in Makassar follows the schedule of the Indonesian Ministry of Religion, but for dawn it refers to the decision of the 31st Muhammadiyah Tarjih National Conference with an additional 8 minutes. The public response, both from Muhammadiyah and NU, was generally positive as a form of caution. The implications of this study indicate that the lack of socialization about the change in the beginning of the dawn prayer time in society has resulted in differences among Islamic mass organizations. The community also needs to maintain unity, tolerance, and Islamic brotherhood in responding to differences in ijtihadiyah.